Logic-based ontology comparison and module extraction, with an application to DL-Lite - Kontchakov, Roman; Wolter, Frank; Zakharyaschev, Michael (Artificial intelligence, 2010)
We develop a formal framework for comparing different versions of ontologies, and apply it to ontologies formulated in terms of DL-Lite, a family of ‘lightweight’ description logics designed for data-intensive applications. The main feature of our approach is that we take into account the vocabulary (=signature) with respect to which one wants to compare ontologies. Five variants of difference and inseparability relations between ontologies are introduced and their respective applications for ontology development and maintenance discussed. These variants are obtained by generalising the notion of conservative extension from mathematical logic and by distinguishing between differences that can be observed among concept inclusions, answers to queries over ABoxes, by taking into account additional context ontologies, and by considering a model-theoretic, language-independent notion of difference. We compare these variants, study their meta-properties, determine the computational complexity of the corresponding reasoning tasks, and present decision algorithms. Moreover, we show that checking inseparability can be automated by means of encoding into QBF satisfiability and using off-the-shelf general purpose QBF solvers. Inseparability relations between ontologies are then used to develop a formal framework for (minimal) module extraction. We demonstrate that different types of minimal modules induced by these inseparability relations can be automatically extracted from real-world medium-size DL-Lite ontologies by composing the known tractable syntactic locality-based module extraction algorithm with our non-tractable extraction algorithms and using the multi-engine QBF solver aqme. Finally, we explore the relationship between uniform interpolation (or forgetting) and inseparability.